Effect of sol-gel synthesized BiFeO3 nanoparticle addition in YBa2Cu3O7–δ (Y123) superconductor synthesized by standard solid state reaction method - Bahboh, Abdalla; Shaari, Abdul Halim; Baqiah, Hussein; Chen, Soo Kien; Awang Kechik, Mohd Mustafa; Abdib Talib, Zainal; Dihom, Mustafa Mousa (Trans Tech Publications, 2019)
The effects of the multiforric BiFO3 nanoparticles addition on the structure and superconducting properties of YBa2Cu3O7–δ (Y123) with different concentrations were systematically investigated using X-ray diffraction (XRD), field emission scanning electron micrograph (FESEM), EDX and four point probe measurement. It was found that the added samples were predominant by Y-123 phase beside small amount of Y-211 and unreacted BiFeO3 secondary phases. Samples with less (wt.%) BFO added YBCO precursor powder preserved the orthorhombic structure similar to the pure YBCO, while samples with higher wt% addition show orthorhombic-to-tetragonal transition tendency. The samples became more porous and their grain size slightly decreased with addition of BiFeO3. The addition of nanoBiFeO3 disturbed the grain growth of Y123, thus resulting in the degradation of superconducting properties of the samples. The superconducting transition temperature (Tc onset) of samples decreased from 92 K for x=0.0 to 44 K for x=10.0 wt. %, which could be attributable to oxygen vacancy disorder.